Social and spatial continuities and differentiations among Portuguese ciganos: regional profiles - Mendes, Maria Manuela (2016)
The coexistence of people and societies marked by ethnic, social, cultural, religious and linguistic diversity is a subject that still generates controversies in contemporary societies. The “Ciganos’ situation” is an unavoidable issue that crosses the boundaries of different European countries, which leads to controversy and ambivalence in the so-called multicultural and/or intercultural societies characterised by the principle of universalism. In Portugal, despite the social and economic transformations that have occurred, the problems of exclusion and poverty among Ciganos persist. They are still considered the poorest ethnic group, with the worst housing conditions, lest schooling and the main target of racism and discrimination. The Portuguese Ciganos are not a homogeneous community. The diversity and plurality are not always easy to grasp by the glare generated by the adoption of interpretive perspectives that are reductively linear and deterministic of the Portuguese Ciganos. For the purpose of outlining a national picture of Portuguese Ciganos, a national study was developed that combines both qualitative and quantitative methodological approaches. The central goal of this article is to present the main results obtained through a questionnaire survey carried out to Ciganos persons and to discuss the social and spatial continuities and differentiations among Ciganos in Portugal.